Islam Wasatiyah dan Kontestasi Wacana Moderatisme Islam di Indonesia - Muhammad Ainun Najib; Ahmad Khoirul Fata (Jurnal Theologia, 2020)
Moderate Islamic discourse began to develop in Indonesia in early 2015. One such discourse is Islam Wasatiyah. Using the historical method of thought, this article answers three questions. First, the historical background of the Wasatiyah Islamic discourse in Indonesia. Second, Wasatiyah Islam which was conceptualized by religious organizations and Indonesian Muslim scholars. Two important subjects that introduced Wasatiyah Islam in Indonesia are the Indonesian Ulama Council (MUI) and Azyumardi Azra. Third, at almost the same time, the Wasatiyah Islamic discourse competed against Islamic moderatism with other Indonesian Islamic discourses, such as the Islam of the Nahdaltul Ulama and the Advancing Islam of Muhammadiyah. This article finds the correlation between Wasitiyah Islamic discourse in Indonesia and Wasatiyah Islam which originated from the ideas of Malaysian intellectual, Mohammad Hashim Kamali. Wasatiyah Islam in Indonesia, as initiated by Mohammad Hashim Kamali, gave rise to a moderate and tolerant Islam which was based on the values contained in Islam. Like fertile land, Indonesian Islam has indeed become a nursery and contestation of various Islamic discourses, both from Indonesia and abroad. In this article it is also found that a massive support base will mainstream the discourse itself. Therefore, the Wasatiyah Islamic discourse does not have sufficient resonance for the breeding of Islamic moderation in Indonesia, and is drowning in the midst of other Islamic discourses.